Literasi Digital Guru dan Pendidikan Masa Depan: Studi Fenomenologi pada Guru-guru MTs Mambaul Ihsan Larangan Perreng Pragaan Sumenep - Farhan; Ghozi Mubarok (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2026)
In the era of globalization and rapid technological development, digital literacy has become a key competency for educators, including Madrasah Tsanawiyah (MTs) teachers. This study, titled